Pengaruh Kecerdasan Spritual terhadap Hasil Belajar Matematika Siswa - Afrianti Afrianti; M. Imamuddin (Lattice Journal : Journal of Mathematics Education and Applied, 2022)
In addition to intellectual intelligence and social intelligence, spiritual intelligence must be strongly possessed by students in helping and welcoming this continuously complex life. Students' spiritual intelligence is able to bridge the behavior that leads to positive student behavior. In addition, spiritual intelligence is able to lead students not only to improve student spirituality, but also be able to direct students to a better life in the world, especially in the hereafter. This study aims to determine or analyze the influence of students' spiritual intelligence on the mathematics learning outcomes of class VIII SMP Palupuh. Sampling was taken randomly with totaling 45 students. The instrument used is a spiritual intelligence questionnaire to collect data related to students' spiritual intelligence. Meanwhile, data collection on students' mathematics learning outcomes was carried out with documentation from the results of the Student Final Assessment (PAS). Data were analyzed by simple regression and hypothesis testing using t-test. The results of this study explain that the higher the religious level of students, the higher the student learning outcomes. In addition, based on the hypothesis test, it was obtained that students' spiritual intelligence had a significant effect on students' mathematics learning outcomes. It is expected that mathematics teachers are able and always develop students' spiritual intelligence by using Islamic integrated mathematics learning.Selain kecerdasan Intelektual dan kecerdasan sosial, maka kecerdasan spritual harus kuat dimiliki oleh siswa dalam membantu dan menyongsong hidup yang terus menerus kompleks ini. Kecerdasan spritual siswa mampu menjembatani perilaku yang mengarah kepada perilaku positif. Selain itu, kecerdasan spritual mampu mengantarkan siswa tidak hanya untuk meningkatkan spritualitas, tetapi juga mampu mengarahkan diri siswa kepada kehidupan yang lebih baik di dunia dan di akhirat kelak. Penelitian ini bertujuan untuk mengetahui atau menganalisis pengaruh kecerdasan spritual terhadap hasil belajar matematika siswa kelas VIII SMP Palupuh. Pengambilan sampel diambil secara acak yang berjumlah 45 siswa. Instrumen yang digunakan adalah angket kecerdasan spritual untuk mengumpulkan data terkait kecerdasan spritual siswa. Sedangkan pengumpulan data hasil belajar matematika dilakukan dengan dokumentasi dari hasil Penilaian Akhir Siswa (PAS). Data dianalisis dengan regresi sederhana dan uji hipotesis dengan menggunakan uji-t. Hasil penelitian ini menjelaskan bahwa semakin tinggi tingkat religius siswa maka semakin tinggi hasil belajar siswa. Selain itu, berdasarkan uji hipotesis diperoleh bahwa kecerdasan spritual siswa berpengaruh signifikan terhadap hasil belajar matematika siswa. Diharapkan guru-guru matematika mampu dan selalu mengembangkan kecerdasan spritual siswa dengan pembelajaran matematika yang terintegrasi Islam.